Bahasa dan Gender dalam Film Kartun Go Diego Go dan Dora the Explorer: Sebuah Kajian Sosiolinguistik - Haira Rizka (UIN Raden Mas Said Surakarta, 2018)
This research aims to (1) analyze linguistic characteristics of main characters of Go Diego Go and Dora the Explorer; (2) describe social and cultural factors influencing the use of their linguistic characteristics; and (3) describe gender representation reflecting in the movies. The research problems are investigated by employing Pan’s theory of language and gender (2011). This is a descriptive qualitative research. The data source of this research is Go Diego Go and Dora the Explorer movies with 2 randomly selected episodes. The data were collected through observation and note taking technique. The collected data were then analyzed by employing textual analysis method. The research reveals that (1) Dora uses more standard form of phonology, uses more emotional and hyperbole vocabulary, and topics related to daily activity, while Diego does not show these characteristics; (2) the two characters do not use rude or taboo words, question tag, and hyper-correction; (3) different-social status and roles are the factors of different-linguistic characteristics; and (4) gender stereotype reveals that Diego to tell science and technology, while Dora to tell domestic stories and neighborhood.